Reshaping geochemical fate of gold-mining-derived arsenic in Jiehe River sediments from molecular to field scales via an innovative iron-based mineralization strategy - Weichen Luo; Ting Li; Yujun Zhou; Baoting Ding; Xin Du; Xuan Liu; Yongpeng Zhang; Zhaodi Wu; Jianru Liang; Shuqing Li; Jun Chen; Lixiang Zhou (Water Research, 2026)

Bifunctional antifouling strategy based on polypeptide hydrogels for enhancing long-term stability of potassium ion sensors in complex systems - Wenjing Tai; Weichen Meng; Xuning Liu; Enbao Lu; Tianyu Zhang; Xiujuan Qiao; Xianghua Zeng; Zhanfeng Li; Xiliang Luo (Analytica Chimica Acta, 2026)

Highly efficient stabilization of arsenic in the contaminated sediments of Jiehe River by schwertmannite to inhibit arsenic release into overlying water - Weichen Luo; Ting Li; Yan Dong; Yujun Zhou; Zhaodi Wu; Xuan Liu; Jiahao Ni; Jingang Xu; Dejin Zhang; Mingjiang Zhang; Di Fang; Lixiang Zhou (Journal of Hazardous Materials, 2025)

The Contributions of Cultivar and Fertilization Improvements to Single Rice Nitrogen Use Efficiency Trends Across China - Xinjie Ju; Xin Liu; Wenjun Jiang; Hao Liang; Pete Smith; Jiafa Luo; Weichen Huang; Wulahati Adalibieke; Jin Fu; Feng Zhou (Global Change Biology, 2025)
Nitrogen use efficiency (NUE) serves as a useful performance indicator to benchmark agricultural nitrogen management. It is determined by genotype‐environment‐management interaction, making the quantification of the key drivers and the mechanism behind spatiotemporal trends of NUE challenging. In this study, the soil Water Heat Carbon Nitrogen Simulator (WHCNS) model, integrated with multi‐scale datasets, was applied to clarify the key drivers of the NUE trends for single rice in China from 1978 to 2019. The national NUE for single rice was 0.31 over the study period and showed a slight increase before 2005 and afterwards a rapid increase of 0.048/10 years, primarily controlled by fertilization management and cultivar shifts. The N application rate determined the total N input, influenced the N uptake and utilization efficiency, and therefore the NUE, while the effect of cultivar shifts on NUE is mainly determined by the increase in the proportion of photosynthetic products in the rice grain and thus the harvest index. The benefits of cultivar improvement (0.034/10 years) which were almost entirely offset by the excessive use of N fertilizers (−0.029/10 years) before 2005, became lower (0.021/10 years) and unstable thereafter in many subregions, indicating the challenge of cultivar selection under low N inputs. To reach the ambitious NUE target of 0.6 by 2050 for rice, improving NUE through better management alone will not be enough. Improvements in rice breeding are therefore urgently needed to meet future NUE challenges in rice production under climate change and population growth.

Uncovering the dynamic interactions of China's energy-metal nexus from 2005 to 2020 - Weichen Wang; Kaipeng Ren; Xu Tang; Cuiyang Feng; Yuqing Jiang; Pengfei Luo; Mikael Höök (Journal of Cleaner Production, 2025)

The Role of Thrombo-inflammation in Ischemic Stroke: Focus on the Manipulation and Clinical Application - Yuanfei Luo; Weichen Dong; Linying Yuan; Yunqing Amelia Zhu; Dachuan Dustin Zhang; Heyu Ni; Wusheng Zhu (Molecular Neurobiology, 2025)

Fabrication method and various application scenarios of flexible capacitive pressure sensor based on direct formation of conical structure - Xi Wang; Ying Li; Ying Wang; Weichen Huang; Xuanmo Zhao; Kedi Chen; Fanchen Luo; Yafei Qin (Chemical Engineering Journal, 2024)

Essential oils ameliorate the intestinal damages induced by nonylphenol exposure by modulating tryptophan metabolism and activating aryl hydrocarbon receptor via gut microbiota regulation - Chaoyue Ge; Xinyu Luo; Yujie Lv; Lianchi Wu; Zhaoying Hu; Weichen Huang; Shenao Zhan; Xinyu Shen; Cai Hui; Dongyou Yu; Bing Liu (Chemosphere, 2024)

Complex sliding characteristics of landslides and evaluation of the reinforcement with arched anti-slide piles based on 3D discrete element method: a case study - Qiang Xie; Zhilin Cao; Renjun Tian; Weichen Sun; Alessio Fumagalli; Haiyou Peng; Xiang Fu; Haoyang Luo (Natural Hazards, 2024)

A highly stable electrochemical sensor with antifouling and antibacterial capabilities for mercury ion detection in seawater - Weichen Meng; Xiaochun Han; Rui Han; Xinchao Zhang; Xianghua Zeng; Jizhou Duan; Xiliang Luo (Analytica Chimica Acta, 2024)

A low-fouling electrochemical biosensor based on BSA hydrogel doped with carbon black for the detection of cortisol in human serum - Xiaohang Yu; Weichen Meng; Yang Li; Xiliang Luo (Analytica Chimica Acta, 2024)

Cryogenian and Ediacaran integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Lang Sun; Malik Muhammad Saud Sajid Khan; Chuan Yang; Zhixin Sun; Bing Pan; Shehryar Ahmed; Lanyun Miao; Weichen Sun; Chunlin Hu; Xiaojuan Sun; Cui Luo; Bo Chen; et al. (Science China Earth Sciences, 2024)

Modeling denitrification nitrogen losses in China's rice fields based on multiscale field‐experiment constraints - Huayan Zhang; Wulahati Adalibieke; Wenxin Ba; Klaus Butterbach‐Bahl; Longfei Yu; Andong Cai; Jin Fu; Haoming Yu; Wantong Zhang; Weichen Huang; Yiwei Jian; Wenjun Jiang; et al. (Global Change Biology, 2024)
Denitrification plays a critical role in soil nitrogen (N) cycling, affecting N availability in agroecosystems. However, the challenges in direct measurement of denitrification products (NO, N 2 O, and N 2 ) hinder our understanding of denitrification N losses patterns across the spatial scale. To address this gap, we constructed a data‐model fusion method to map the county‐scale denitrification N losses from China's rice fields over the past decade. The estimated denitrification N losses as a percentage of N application from 2009 to 2018 were 11.8 ± 4.0% for single rice, 12.4 ± 3.7% for early rice, and 11.6 ± 3.1% for late rice. The model results showed that the spatial heterogeneity of denitrification N losses is primarily driven by edaphic and climatic factors rather than by management practices. In particular, diffusion and production rates emerged as key contributors to the variation of denitrification N losses. These findings humanize a 38.9 ± 4.8 kg N ha −1 N loss by denitrification and challenge the common hypothesis that substrate availability drives the pattern of N losses by denitrification in rice fields.

Significant insights of Cu and Fe as key metals to cause RO membrane fouling under coal-mining wastewater treatment - Lequn Sun; Weichen Lin; Danyang Li; Kang Xiao; Daoyi Chen; Shuai Luo; Xia Huang (Desalination, 2023)